Pengenalan Artificial Intelligence sebagai Asisten Digital dalam Penulisan Artikel Ilmiah bagi Dosen di STAK Arastamar Grimenawa Jayapura - Ismail, Jeffrit Kalprianus; Gulo, Rezeki Putra; Rangga, Oktavianus (Jurnal PKM Setiadharma, 2025)
This Community Service Program was conducted at STAK Arastamar Grimenawa Jayapura from January 13-15, 2025. The background of this service stems from the need to enhance lecturers' competencies in utilizing AI technology as a digital assistant for academic writing. The program aims to introduce and train lecturers in using AI technology responsibly to produce high-quality scientific works that align with Christian values. The implementation method comprises five stages: observation, planning, training execution, academic study writing, and evaluation. The novelty of this service lies in integrating technical aspects of AI usage with Christian spiritual values in the context of academic writing at theological education institutions. The results show significant improvement in lecturers' ability to utilize AI applications to enhance grammar quality, originality, and structure of scientific articles while maintaining spiritual and academic integrity. This program successfully bridges academic needs with theological missions through ethical and responsible use of AI technology.